Peran Orang Tua Terhadap Pendidikan Anak Usia Dini Dalam Pandangan Islam - denny erica; Haryanto Haryanto; Mari Rahmawati; Irwin Ananta Vidada (UIR Press, 2021)
From an Islamic point of view, children are a mandate given by Allah to their parents, to provide good and healthy education, involving families is a place for children to learn, communicate, communicate, and behave towards the environment associated with it, and a children will always need a lot of attention and affection from both parents. The role of parents in the development of early childhood education from an Islamic point of view must be able to provide an explanation of all the children born in a state of nature, instill monotheism and aqeedah truly to children, teach children to help prayer, teach children to read the Koran, motivate children to always pray, teach children to always be grateful, motivate children to worship at the mosque, teach children to always be naked, teach children to always maintain the cleanliness of the body, and teach children to love each other God's creatures. By involving parents in providing education that contains Islamic religious values, it is expected that these early childhood children can support the process of adaptation to the outside environment, bearing in mind that these early childhood have strong character and faith in the process of development of growth and development for child.